ANALISIS GEOLOGI WILAYAH SUNGAI CINAMBO MENDUKUNG KESINAMBUNGAN KEMANFAATAN WADUK JATIGEDE, JAWA BARAT - Sofyan Rachman; Harry Pramudito (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2016)
Cinambo River is one of the rivers that enter the watershed Cimanuk located around the construction area Jatigede Dam. Based on the plan Jatigede Dam, Cinambo River are included in the inundation area, where at a future time will be puddles of Jatigede Dam. The appearance of the river, geology and geomorphology phenomena around the river will disappear puddles drowned by the reservoir. The efforts to save geological data of surrounding Cinambo River are necessary to documented so that the results can be useful. Many aspects of the geological data that can be used to good engineering the spread land movement, slope stability, land stability and the area development. Future studies related to Cimanuk river basin area will always refer to the data around Cinambo River.